Modeling the Impact of Fat Flexibility With Dairy Food Servings in the 2015–2020 Dietary Guidelines for Americans Healthy U.S.-Style Eating Pattern - Hess, Julie M.; Cifelli, Christopher J.; Fulgoni, Victor L. (Frontiers in Nutrition, 2020)
Background: The 2015-2020 Dietary Guidelines for Americans (DGA) recommends consuming low-fat or fat-free dairy foods due to concerns about energy and saturated fat intake. It also recommends consuming no more than 10% of daily calories from saturated fat. Objective: The objective was to assess the impact of replacing one serving of fat-free dairy foods in the Healthy U.S.-Style Eating Pattern (HUSEP) from the DGA with one serving of whole- or reduced-fat dairy foods. We hypothesized that this replacement would keep the HUSEP within calorie, saturated fat, and sodium limits. Methods: Utilizing the same modeling procedures as the 2015-2020 DGA, we assessed the nutrient composition of seven alternative models of the 2000-calorie HUSEP. These models replaced all three servings of dairy foods in the HUSEP with an updated fat-free dairy composite (Model 1) or one of three fat-free dairy servings in the HUSEP with: a whole-fat dairy food composite, a reduced-fat/low-fat dairy food composite, whole milk, reduced-fat milk, whole-fat cheese, or reduced-fat cheese (Models 2-7). Results: In all models, the amount of saturated fat did not exceed 10% of total calories, but the amount of energy increased by 45- 94 calories. While still lower than current average intake (3,440 mg/d), sodium amounts in four of the seven models exceeded the 2,300 mg/d recommended intake level. Conclusions: Some reduced- and whole-fat dairy foods, especially milk, can fit into calorie-balanced healthy eating patterns that also align with saturated fat recommendations. Allowing some flexibility in fat level of dairy food servings aligns with the recommendations that calories from solid fats and added sugars are best used to increase the palatability of nutrient-dense foods.